2015
DOI: 10.1016/j.compositesb.2015.03.080
|View full text |Cite
|
Sign up to set email alerts
|

Green composites based on polypropylene matrix and hydrophobized spend coffee ground (SCG) powder

Abstract: Green composites were prepared with polypropylene matrix and 20 wt.% spent coffee ground (SCG) powder for uses as a wood plastic composite (WPC). The effects of hydrophobic treatment with palmitoyl chloride on SCG powder is compared with conventional surface treatment based on silanization with (3-glycidyloxypropyl) trimethoxysilane and the use of a maleated copolymer compatibilizer (polypropylene-graft-maleic anhydride, PP-g-MA) in terms of mechanical properties, morphology, thermal properties and water uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
115
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(127 citation statements)
references
References 53 publications
(47 reference statements)
10
115
1
1
Order By: Relevance
“…So, more energy for debonding and fiber pull-out is required and the composite impact strength increases (Nygård et al 2008). García-García and coworkers also observed an improvement in the impact strength after the addition of polypropylene grafted maleic anhydride in composites of polypropylene reinforced by coffee ground powder (García-García et al 2015). The authors attribute this improvement to the strong interactions among particle-polymer at the interface.…”
Section: Mechanical Propertiesmentioning
confidence: 71%
“…So, more energy for debonding and fiber pull-out is required and the composite impact strength increases (Nygård et al 2008). García-García and coworkers also observed an improvement in the impact strength after the addition of polypropylene grafted maleic anhydride in composites of polypropylene reinforced by coffee ground powder (García-García et al 2015). The authors attribute this improvement to the strong interactions among particle-polymer at the interface.…”
Section: Mechanical Propertiesmentioning
confidence: 71%
“…In recent years, there have only been a handful of published studies in this area. These have mostly focused on SCG biocomposites with polymers including poly(lactic acid) (Baek et al 2013;Lee et al 2015a;Wu 2015), polypropylene (Jaya Chitra et al 2014;García-García et al 2015), recycled high-density polyethylene (Cestari et al 2013), and poly(vinyl alcohol) (Lee et al 2015b). After extensive research, only one publication on CC composites, with feather keratin polymer, was found (Barone 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, polyethylene or polypropylene fraction in PE-g-MA and PP-g-MA respectively 4 can interact with some polymer chains due to chemical affinity while maleic anhydride groups in the compatibilizer structure can react with hydroxyl groups in ligno-cellulosic particle by an esterification reaction to give increased matrix-filler interactions which have a positive effect on particle dispersion and stiffness. 13,18 Despite this, ductile properties are not usually improved due to the brittleness that the filler provides because of presence of particle aggregates and matrix discontinuity, which promote stress concentration phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…This fact, together with the problems related to petroleum depletion has led to a breakthrough in the field of environmentally friendly materials development; much of this progress has been observed in the field of polymer composites, mainly on natural fiber reinforced plastics (NFRP) and wood plastic composites (WPC) for everyday applications. [1][2][3][4] The use of natural fillers into a polymeric matrix provides attracting advantages such as reduced costs, lightness, excellent balanced mechanical properties, etc. together with a marked low environmental impact.…”
Section: Introductionmentioning
confidence: 99%